Emission Brightness and Concentration Quenching Threshold of GdVO4 : Eu3+ Nanophosphors Co‐Doped with Alkali Metal Ions. Issue 47 (14th December 2021) - Yang, Yuanyuan; Yan, Yinglin; Fan, Chaojiang; Zou, Yiming; Wang, Juan; You, Caiyin; Yang, Rong
Abstract: GdVO4 : Eu 3+ nanophosphors co‐doped with alkali metal ions (Li +, Na +, K + ) of various concentrations were fabricated by an efficient hydrothermal method. The microstructure and luminescent emission properties were tested systematically. The results demonstrated that the co‐doping of M + led to lattice distortion, which is closely related to dopants' ionic radii and concentrations. The lattice distortion further resulted in a fluctuation of luminescent brightness. The optimal luminescent properties of GdVO4 : Eu 3+ co‐doped with Li + (10 atom‐% (at. %)), Na + (8 at. %), K + (6 at. %) were achieved respectively. Among them, the GdVO4 : Eu 3+ co‐doped with Li + of 10 at % possessed the highest emission intensity. Moreover, the alkali metal ions co‐doping also gave rise to the elevation of the concentration quenching threshold of Eu 3+, which further enhanced the luminescent performance. Abstract : The GdVO4 : Eu 3+ nanophosphors co‐doped with alkali metal ions (M +, M=Li, Na, K) were prepared. When co‐doped with a small amount of Li + (2 at. %), it replaces the Gd 3+ site and the single‐crystal cell shrinks significantly. When co‐doped with more Na + /K + ions, the larger ion diameter leads to structural distortion. The results show that the luminescence properties of Eu 3+ are affected by M + radius and concentration, and the optimal emission brightness and concentration quenching threshold of Eu 3+ evolve with the radiation of M + .